2020
DOI: 10.1017/s0959270920000568
|View full text |Cite
|
Sign up to set email alerts
|

The state of breeding birds in Greece: trends, threats, and implications for conservation

Abstract: Summary Birds are suffering from steep population declines on a global scale and they are one of the few taxonomic groups for which these declines are well documented by long-term monitoring data. This study provides a synthesis of the status of the breeding birds of Greece. To this aim, we retrieved population size estimates from six sources spanning 22 years (1992–2014) and calculated species’ trends in Greece. Using the IUCN Red List assessments for each species we assessed whether ecological traits incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Similar findings are reported in [2], and [45] who have found that both the short-and the long-term population trend of the species is stable in Greece. A recent study for 246 breeding birds in Greece finds an increasing trend for the species in Greece, similar to our finding, as indicated by the hunting sustainability index [46].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings are reported in [2], and [45] who have found that both the short-and the long-term population trend of the species is stable in Greece. A recent study for 246 breeding birds in Greece finds an increasing trend for the species in Greece, similar to our finding, as indicated by the hunting sustainability index [46].…”
Section: Discussionsupporting
confidence: 92%
“…The European Goldfinch and the European Greenfinch, which showed strong decreasing trends, are listed as “near threatened”. Although our results are at regional scale, they can provide valuable information for updating local, national and continental Red Lists [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although species population trends are not directly informative on drivers of population changes [ 21 ], observing a common trend among species with similar ecological or life history traits can provide the foundation to test specific hypotheses about the drivers of the observed population dynamics [ 22 ]. Despite the arising attention of a trait-based approach in community ecology [ 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and population ecology [ 30 , 31 , 32 , 33 , 34 ], only in the last few years researchers have started to explore the link between traits and population trends in avifauna over long time periods, highlighting the existence of different patterns among distinct functional groups [ 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such it is of special importance, especially considering the fact that since 1980, Eurasian skylark populations have suffered a moderate decline (up to 50%) in Europe ( (Keller et al 2020;PECBMS database 2021), as well as in England since the mid-1970s (Browne et al 2000). On the contrary, the Eurasian skylark's population size in Greece has increased by 96.5% between 1992 and 2014 (Vavylis et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Declines in wet grasslands in Britain had been steeper than other breeding habitats (Wilson & Vickery 2005). In Greece, its population size has been increasing by an average of 8.3% per year from 1992 to 2014 (Vavylis et al 2020). The Corn bunting has also suffered severe population declines and losses in distribution in Europe mostly due to various kinds of changes in agricultural practices (Keller et al 2020).…”
Section: Discussionmentioning
confidence: 99%